Evaluation of the non-auditory neurocognitive test MoCA-HI for hearing-impaired - Völter, Christiane; Fricke, Hannah; Götze, Lisa; Labrenz, Franziska; Tokic, Marianne; Wirth, Rainer; Nasreddine, Ziad S.; Dawes, Piers (Frontiers in Neurology, 2022)
Background Since hearing loss and cognitive decline often co-occur among older adults, a cognitive screening test suitable for hearing-impaired people is of high clinical relevance. We report the first evaluation of a German language version of the Montreal Cognitive Assessment—Hearing Impaired version (MoCA-HI). Objective The aim of the present study was to compare cognitively healthy participants with and without hearing loss, to examine the impact of age, sex, educational level and degree of hearing impairment on the German MoCA-HI performance, and to develop normative data. Material and methods The German MoCA-HI was tested in 94 participants with normal or mild hearing impairment (group 1: 4PTA ≤ 40 dB on the better hearing ear) and 81 participants with moderate to profound hearing loss (group 2: 4PTA > 40 dB on the better hearing ear). Additionally, all participants performed the standard MoCA (version 8.2). Results No significant group difference between group 1 and 2 was found in the MoCA-HI total score (p = 0.05). In contrast, group 1 performed significantly better than group 2 on the standard MoCA (p < 0.001). There was no difference between the MoCA and the MoCA-HI performance in group 1 (p = 0.12), whereas individuals of group 2 performed significantly better on the MoCA-HI than on the standard MoCA (p < 0.001). Test-retest reliability of the MoCA-HI was high (p < 0.001). Higher age (p < 0.001), male sex (p = 0.009) and lower education (p < 0.001) were associated with a lower overall MoCA-HI score. Based on the demographic data normative data were developed by a regression-based approach. Conclusion The MoCA-HI is a cognitive screening test which is suitable for people with hearing impairment.